Germinal matrix-intraventricular hemorrhage and posthemorrhagic ventricular dilatation in the preterm infant - (:unkn) unknown (Springer International Publishing, 2019)
Germinal matrix-intraventricular hemorrhage (GMH-IVH) is a serious problem in the small preterm infants. The hemorrhage originates from the germinal matrix with an immature capillary bed. The etiology of IVH is complex and multifactorial and is primarily based on the intrinsic fragility of the germinal matrix vessels and the disturbance in the cerebral blood flow. Premature infants with severe IVH are at high risk of posthemorrhagic hydrocephalus, cerebral palsy, and mental retardation. Even infants with mild IVH are at risk of developmental disabilities. Approximately 30-50% of infants, who had severe IVH, develop posthemorrhagic ventricular dilatation, and 20-40% of these cases require permanent ventriculoperitoneal shunt. The main aims of the intervention carried out in posthemorrhagic ventricular dilatation (PHVD) are to minimize the need for the VP shunt and to prevent the secondary damage to the brain caused by the pressure, inflammation, and free radicals. The optimal clinical management of PHVD still remains unclear.A most common approach today is the temporary treatment of hydrocephalus with ventricular access device, ventriculosubgaleal shunt, and less frequently external ventricular drains (EVD). Ventriculoperitoneal shunt is still the main surgical procedure. © Springer Nature Switzerland AG 2019. All rights reserved.
Keywords: Germinal matrix; Hydrocephalus; Intraventricular hemorrhage; Posthemorrhagic ventricular dilatation; Preterm